Tuning the electrical conductivity of amorphous carbon/reduced graphene oxide wrapped-Co3O4 ternary nanofibers for highly sensitive chemical sensors. Issue 48 (29th November 2019) - Feng, Qiuxia; Zeng, Yamei; Xu, Pengcheng; Lin, Shiwei; Feng, Chao; Li, Xiaogan; Wang, Jing
Abstract : The electrical conductivity of amorphous carbon/reduced graphene oxide(rGO)-wrapped Co3 O4 nanofibers prepared by the electrospinning process is for the first time finely tuned creatively by the thermal-etching process in a controlled O2 environment. Abstract : The electrical conductivity of amorphous carbon/reduced graphene oxide(rGO)-wrapped Co3 O4 nanofibers prepared by the electrospinning process is for the first time finely tuned creatively by the thermal-etching process during which the amorphous carbon is removed and the further growth of Co3 O4 nanocrystals within amorphous carbon occurs through thermal oxidation. The influence of electrical conductivity on the room-temperature ammonia sensing properties of these ternary composite material based sensors can thus be investigated for the first time. The fabricated chemiresistive-type sensor using the ternary sample thermally oxidized at 390 °C in a controlled O2 environment shows a good sensitivity and fast response (∼20 s: 50 ppm) to different concentrations of ammonia from 1–100 ppm at room temperature. The sensor demonstrates an excellent selectivity to several possible interferents such as methanol, ethanol, formaldehyde, methylbenzene, benzene, acetone and water and a brilliant long-term stability for about four years. Density functional theory (DFT) calculations are performed to study the coupling effect at the interface of graphene/Co3 O4 (110B) which plays a crucial role in the sensing performance to NH3 . The underlying chemical sensing process is examined using in situ Fourier transform infrared spectroscopy (FTIR) which shows a water-mediated catalytic oxidation transducing mechanism.